QUALITY OF POSTTEST ITEMS ADMINISTERED BY LANGUAGE CENTER (PUSBA) IAIN RADEN INTAN LAMPUNG - Wijaya, M. Sayid (Universitas Islam Negeri Raden Intan Lampung, 2015)
In achieving learning objectives, it needs a test to measure students’ achievement. A test should be constructed based on the learning objectives so it measures what it really intends to measure. It also should be assured that it fulfills the criteria of good test, one of which is item validity. Item validity concerns on how each item measures what has been established in blueprint. However, analyzing item validity is insufficient since it is only a part of item analysis. Therefore, the urge to analyze item quality is imperative. Further, the posttest instrument used in measuring students’ achievement after following matriculation program in IAIN Raden Intan Lampung has not been analyzed yet since the matriculation program operated. In this case, the quality of test items is crucial to be analyzed. In analyzing quality of test items, ANATES was employed to investigate item discrimination, item difficulty, and item validity for practicality and efficiency. The result demonstrated that posttest instrument needed to be revised in terms of item difficulty and effectiveness of distractors.